Answer:
C. x=30
Explanation:
Simply both sides of the equation
8x−3(2x−4)=3(x−6)
8x+(−3)(2x)+(−3)(−4)=(3)(x)+(3)(−6)(Distribute)
8x+−6x+12=3x+−18
(8x+−6x)+(12)=3x−18(Combine Like Terms)
2x+12=3x−18
2x+12=3x−18
Step 2: Subtract 3x from both sides.
2x+12−3x=3x−18−3x
−x+12=−18
Step 3: Subtract 12 from both sides.
−x+12−12=−18−12
−x=−30
Step 4: Divide both sides by -1.
![(-x)/(-1) =(-30)/(-1)](https://img.qammunity.org/2021/formulas/mathematics/high-school/hn7jzakha9mxpnwuffd66hmcchoj3htnmx.png)
x=30
Hope this helps!